Miltefosine, an FDA-approved drug for the 'orphan disease', leishmaniasis. (June 2015) - Berman, Jonathan
<x xml:space="preserve">Abstract</x> Introduction: Leishmaniasis, and most tropical diseases, are rare/orphan diseases in the developed world but not rare worldwide. Classic treatment is with parenteral agents, namely, pentavalent antimony and amphotericin B deoxycholate. <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=Miltefosine&logicalOpe1=OR&field2=articletitle&text2=Miltefosine&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">Miltefosine is the first oral agent for all forms of leishmaniasis. The target regimen is 2.5 mg/kg/day for 28 days, with a maximum dose of 150 mg/day (one 50 mg capsule each with breakfast, lunch and dinner). Areas covered: Clinical studies visceral, cutaneous and mucosal leishmaniasis treated with miltefosine. Expert opinion: The 2014 FDA approval of the miltefosine New Drug Application for visceral, cutaneous and mucosal leishmaniasis was a breakthrough in several ways. In a clinical sense, miltefosine was recognized in the US, after previously being approved in Europe and in the developing world, as the first oral treatment for any form of leishmaniasis. In a regulatory sense, miltefosine was the first drug solely developed for leishmaniasis. In a financial sense, the $125 million sale of miltefosine's Tropical Disease Priority Review Voucher created a financial incentive for all tropical disease products. Clinical issues remaining post-approval include generalizability of efficacy data generated against the specific species evaluated in registration documents to the large number of species worldwide and tolerance issues partially addressed pre-registration.